An Application of Social Capital Theory in Supply Chain: A Case of Thai Global Buyer Firms - Luedech Girdwichai; Pornkul Suksod; Mallika Saenpakdee; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
The current study has placed an effort to disclose the application of the social capital theory in the supply chain. The Thai global buyers’ firms are taken as the final sample of the study. The SEM-PLS is used to analyze the data. It has been revealed in the present research that the focus of social capital is on the creation and knowledge sharing within and across the organizations. This is also indicated by the current research. It has been argued by the prior studies that the use of different organization and outcomes of social capital will benefit the future research including the factors of cost, quality, and flexibility. It has been indicated by the results of current research that social capital theory can be applied to the relation of buyer and supplier with reference to the development of supplier. The statement that there is need for more investigation for the various dimensions of social capital related to relational embeddedness, structural embeddedness and cognitive dimension. It is found that the achievements of buyer performance in the form of total cost is explained by the relational capital in terms of buyer-supplier dependence and cognitive capital in shared values, and structural capital in terms of activities of supplier development. Cognitive capital and relationship commitment are the common explanatory variables for the both performance dimensions.